"MOM, I CAN SPEAK ENGLISH!": CASE STUDY OF THE USE OF FLASHCARDS ON EARLY CHILDHOOD CHILDREN - Siti Mafulah; Ni Nyoman Ayu Shri Smertini Adhi ((JIBS) JURNAL ILMIAH BAHASA DAN SASTRA, 2024)
Children language acquisition is depended on the learning situation, engagement, and the use of media. Therefore, this study investigates the use of flashcards as media on children ‘s vocabulary mastery. This study focused on the children’s, parents, and teacher’s perception. This study used qualitative research design. To obtain data, observation and interview were applied. The observation was done during the teaching learning process while interview for the children was given whenever the children were in a good mood. The findings revealed the challenges and benefits of using flashcards for early childhood learning. Children showed strong involvement and retention when they were engaged in the learning process using flashcards. Besides, the combination between the use of flashcards and games made the learning process more interactive. The teacher emphasized the usefulness of flashcards to enhance participation and memory retention. Besides, based on the parents’ point of view, the use of Flashcards is flexible and helps children in speeding up the language acquisition. The study presents new insights into effective language teaching techniques for early childhood with a focus on cognitive needs as well as specific developmental needs of children. It is recommended to use flashcards for educators and parents who want to improve their early childhood language learning experience.